Comparisons of the Relationships Between Multiple Lipid Indices and Diabetic Kidney Disease in Patients With Type 2 Diabetes: A Cross-Sectional Study - Lu, Chun-feng; Liu, Wang-shu; Chen, Zhen-hua; Hua, Ling-yan; Wang, Xue-qin; Huang, Hai-yan (Frontiers in Endocrinology, 2022)
Background Dyslipidemia is a well-recognized risk factor for diabetic kidney disease (DKD) in patients with type 2 diabetes (T2D). Growing evidences have shown that compared with the traditional lipid parameters, some lipid ratios may provide additional information of lipid metabolism. Thus, the present study aimed to investigate which lipid index was most related to DKD. Methods This study was a cross-sectional study that enrolled patients with T2D from January 2021 to October 2021. Each participant was screened for DKD, and the diagnostic criterion for DKD is estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m2 or urinary albumin-to-creatinine ratio (UACR) ≥ 30 mg/g for 3 months. Fasting blood was collected to determine lipid profiles by an automatic biochemical analyzer, and lipid ratios were calculated based on corresponding lipid parameters. Spearman’s correlation analyses were conducted to assess the correlations between lipid indices and kidney injury indices, and binary logistic regression analyses were conducted to explore the relationship between lipid indices and the risk of DKD. Results A total of 936 patients with T2D were enrolled in the study, 144 (15.38%) of whom had DKD. The LDL-C/Apo B ratios were positively correlated with eGFR (r = 0.146, p < 0.05) and inversely correlated to cystatin C and UACR (r = -0.237 and -0.120, both p < 0.001). Multiple logistic regression demonstrated that even after adjusting for other clinical covariates, the LDL-C/Apo B ratios were negatively related to DKD, and the odds ratio (95% confidence interval) was 0.481 (0.275–0.843). Furthermore, subgroup analyses revealed that compared with patients with normal lipid profiles and a high LDL-C/Apo B ratio, the odds ratio of DKD in patients with normal lipid metabolism and a low LDL-C/Apo B ratio was 2.205 (1.136-4.280) after adjusting for other clinical covariates. Conclusion In patients with T2D, the LDL-c/Apo B ratio was most closely associated with DKD among various lipid indices, and a lower LDL-C/Apo B ratio was associated with increased risks of DKD among patients with T2D.